Weighting Sustainability Dimensions: The Drivers Behind Personal Decision-Making - Peltonen, Andrew (My University, 2024)
Sustainability has become a mandatory consideration for firms as it is a fundamental requirement for most businesses through increased regulation and compliance in the business environment of today. Despite this essential need for sustainability, companies and decision-makers struggle with seeking a balance between sustainability dimensions in their practical sustainability efforts. Previous research has illustrated how firms and decision-makers drift from balancing sustainability dimensions to instead prioritizing some sustainability dimensions over others. As a result, they call on the need to investigate drivers that sway personal level of decision-making regarding weighting sustainability dimensions which this thesis aims to examine. This thesis adopted a qualitative approach by applying open-ended and semi-structured interviews of four sustainability professionals from different Finnish companies and organizational levels. The results produced multiple interesting findings. The interviews confirmed and expanded upon multiple different drivers seen from prior literature. This thesis distinguished between mandatory and optional drivers, elaborated on the dominance of the economic dimension, identified a duality of decision-making consisting of both rational and personal elements and proposed a hierarchy of demands between sustainability dimensions. In addition, novel drivers were also identified not previously seen in the literature review. Novel drivers include resource constraints, industry and core mission of the company, level of integration between sustainability and organizational structure, sustainability proficiency of colleagues, personal preferences or values, flexibility in decision-making processes and room for personal preferences and values in daily work. In addition, sustainability professionals were seen to assume the role of an educator and engage in change management practices. The main conclusions center around how sustainability professionals weight sustainability dimensions. First, sustainability professionals consider multiple different aspects when trying to make better decisions in terms of sustainability. Second, a high degree of freedom in decision- making processes enable sustainability professionals to reflect upon their personal values in helping to navigate between various choices related to different sustainability dimensions. Last, sustainability professionals utilize the freedom for personal preferences in their work to make room for values in their decision-making which in turn enables them to apply their scope of values in allocating weight to each sustainability dimension similar to a guiding logic. As a result, personal values help to bridge the gap between decision-making logics and sustainability decision-making regarding the weight of each sustainability dimension. Multiple avenues for future research are introduced. Future research can increase confidence in the novel drivers, examine the relationship between company values and personal values more closely, explore organizational level of decision-making in supporting true sustainability and compare the role of personal preferences and values in different cultural contexts, as their application in decision-making may be highly influenced by cultural differences.

Kestävä kehitys on pakollinen harkinnan kohde yrityksille, koska sen merkitys on korostunut lisääntyneen lainsäädännön ja sääntelyn vuoksi nykypäivän liiketoimintaympäristössä. Tästä välttämättömästä tarpeesta huolimatta yritykset ja päätöksentekijät kokevat käytännön haasteita löytääkseen tasapainon kestävän kehityksen eri ulottuvuuksien välillä. Aiemmat tutkimukset ovat osoittaneet, kuinka yritykset ja päättäjät ajautuvat painottamaan tiettyjä kestävän kehityksen ulottuvuuksia tasapainottamisen sijaan. Näin ollen kirjallisuudessa on nähtävissä erityinen tarve tutkia tekijöitä, jotka vaikuttavat henkilökohtaiseen päätöksentekoon kestävän kehityksen ulottuvuuksien painottamisen osalta. Tätä tämä Pro gradu -tutkielma pyrkii tarkastelemaan. Tässä Pro gradu -tutkielmassa omaksuttiin laadullinen lähestymistapa soveltamalla avoimia ja puolistrukturoituja haastatteluja neljälle vastuullisuuden asiantuntijalle eri suomalaisista yrityksistä ja organisaatiotasoista. Tulokset tuottivat useita mielenkiintoisia havaintoja. Haastatteluissa vahvistettiin ja laajennettiin useita eri tekijöitä akateemisesta kirjallisuudesta. Tutkielmassa eroteltiin pakolliset ja valinnaiset tekijät, käsiteltiin taloudellisen ulottuvuuden valta-asemaa, tunnistettiin päätöksenteon kaksinaisuus, joka koostuu sekä rationaalisista että henkilökohtaisista elementeistä, ja ehdotettiin hierarkiaa kestävän kehityksen ulottuvuuksien vaatimusten välille. Lisäksi tunnistettiin uusia tekijöitä, joita ei havaittu kirjallisuuskatsauksen yhteydessä. Uusia tekijöitä olivat resurssirajoitukset, toimiala ja yrityksen ydintehtävä, kestävän kehityksen ja organisaatiorakenteen välinen integraatio, muiden työntekijöiden kestävän kehityksen osaaminen, henkilökohtaiset mieltymykset tai arvot, joustavuus päätöksentekoprosesseissa ja mahdollisuus hyödyntää henkilökohtaisia mieltymyksiä tai arvoja päivittäisessä työssä. Lisäksi kestävän kehityksen asiantuntijoiden nähtiin omaksuvan opettajan roolin ja osallistuvan muutosjohtamiseen. Tutkimuksen johtopäätökset lisäävät ymmärrystä siitä, kuinka vastuullisuuden asiantuntijat painottavat kestävän kehityksen eri ulottuvuuksia. Kestävän kehityksen asiantuntijat ottavat huomioon useita eri näkökohtia yrittäessään tehdä parempia päätöksiä kestävän kehityksen parissa. Merkittävä vapaus päätöksentekoprosesseissa mahdollistaa vastuullisuuden asiantuntijan pohtimaan omia henkilökohtaisia mieltymyksiä ja arvoja, mitä käytetään apuna erilaisten kestävän kehityksen ulottuvuuksiin liittyvissä valinnoissa. Vastuullisuuden asiantuntijat hyödyntävät työssään esiintyvää vapautta omille henkilökohtaisille mieltymyksille, mikä puolestaan antaa heille mahdollisuuden soveltaa omia arvojaan painottaessaan jokaista kestävän kehityksen ulottuvuutta samaan tapaan kuin päätöksenteon logiikka. Henkilökohtaiset mieltymykset ja arvot täydentävät päätöksentekologiikan ja kestävän kehityksen päätöksenteon välistä kuilua kunkin kestävän kehityksen ulottuvuuden painoarvon osalta. Tulevaisuuden tutkimukselle on useita eri mahdollisuuksia. Tuleva tutkimus voi parantaa luottamusta uusiin päätöksenteon tekijöihin, tutkia tarkemmin yrityksen arvojen ja henkilökohtaisten arvojen välistä suhdetta, tutkia organisaatiotason päätöksentekoa vastuullisuuden tukemisessa ja vertailla henkilökohtaisten mieltymysten ja arvojen roolia eri kulttuureissa.
Keywords: sustainability, sustainable development, decision-making, decision-making logic, weighting decisions, sustainability dimensions, sustainability manager, sustainability professional